EVIDENCE OF LITHOSPHERIC COOLING PRIOR TO MELT INFILTRATION HISTORY AT THE OMAN PALEO-SPREADING CENTRE (WADI TAYIN MASSIF) - Basch, Valentin; Crispini, Laura; Battifora, Caterina; Rampone, Elisabetta (Ofioliti, 2023)
The Oman ophiolites offer exceptional exposure of fossil oceanic lithosphere and have been used as a proxy to define the Penrose model of fast-spread oceanic lithosphere. It is composed of several large massifs in which extensive field mapping allowed to reconstruct the position of several paleo-spreading segments. Yet, the geodynamic setting of formation and evolution of this oceanic lithosphere is still debated, between a mid-ocean ridge and back-arc setting. The southern massifs are widely recognised to best expose the primary accretion of the lithosphere, whereas the northern massifs expose a widespread secondary andesitic magmatic phase. To constrain the geodynamic evolution of the Oman oceanic lithosphere, we investigate the processes registered by the upper mantle section from the Wadi Tayin, sampled during the Oman Drilling Project (Holes CM1A and CM2B). We here provide a petrochemical study of spinel harzburgites and pyroxenites sampled within the uppermost mantle, few tens of meters from the Moho Transition Zone. The main processes that we document are i) the segregation of pyroxenite veins during (reactive) melt percolation at spinel-facies conditions, ii) cooling of the mantle, with partial re-equilibration of the mantle harzburgites and pyroxenites, and iii) reactive porous flow and partial dissolution of mantle pyroxenes. Notably, this chronological evolution involves cooling of the mantle section and incorporation in lithospheric environment prior to the magmatic event leading to percolation of melts through the spinel- to plagioclase-facies lithosphere. Further geochemical studies will allow to constrain the magmatic affinity of percolating melts and the geodynamic setting in which the Oman lithosphere was accreted.